On skew C1C2-Symmetric operators - O. Dakheel, Shireen (Pure Sciences International Journal of Kerbala, 2025)
Let C1 and C2 be conjugation operators, both of which are antilinear, isometric, and involution mappings, defined on a separable complex Hilbert space . This paper introduces the concept of skew -symmetric operators ( -S.O). A bounded linear operator A on is classified as a -S.O. if it satisfies the condition ( C1A = -A⁕ C2 ), or equivalently, ( A = -C1 A* C2 ). We examine and analyze several fundamental properties of such operators and provide a concrete example to illustrate this notion.